Comparative Analysis of Serum Proteins from Patients with Severe and Mild EV‐A71‐induced HFMD using iTRAQ‐Coupled LC‐MS/MS Screening. Issue 11 (2nd November 2017) - Fan, Peihu; Chen, Wei; Yu, Pin; Bao, Linlin; Xu, Lili; Qin, Chuan
Abstract : Purpose: This study was designed to provide a rationale for monitoring the development of severe hand, foot, and mouth disease (HFMD) and predicting the onset of this disease via global comparative analysis between patients with severe and mild HFMD. Experimental design: The authors collected serum from five groups: mild (E‐M) and severe (E‐S) EV‐A71‐induced HFMD; mild (NE‐M) and severe (NE‐S) non‐EV‐A71‐induced HFMD; and healthy control subjects (CON). The authors then performed comparative analysis and identified specific differentially expressed proteins (DEPs) of E‐S using isobaric mass tag (isobaric tags for relative and absolute quantitation, iTRAQ) labeling coupled with multidimensional liquid chromatography‐mass spectrometry (LC‐MS/MS). Moreover, The authors validated specific DEPs by multiple reaction monitoring (MRM). Results: The authors identified 10 specific proteins that were significantly altered in E‐S patients. Bioinformatics analysis revealed that most of these DEPs are primarily involved in the acute response to infection, which was common to all groups. More importantly, up‐regulated proteins associated with neural injury were specifically identified in the E‐S group. Conclusion: These findings conclude that severe HFMD symptoms may be caused by EV‐A71 infection‐mediated injury of the neural system and provide a reference for future research on the course and prognosis of severe HFMD.